Strengthening Youth Science Club by Conducting Basic Research Investigation for “Santri” Students - Titi Fitrianita; Didid Hariyadi; Tamara Adelia Nainggolan; Muhammad Dimas; Muhammad Ikhsan Pratama; Shilva Nursafitri; Dwi Ismiasih (LPMP Imperium, 2024)
This community service is motivated by the shortage of students at Islamic Boarding School to write student scientific papers. The Youth Science Club extracurricular at Islamic Boarding School Daarul Ukhuwah was established to foster a tradition of research and scientific thinking. The initial initiation of KIR stemmed from not all santri graduates continuing their studies in Arab countries; some santri would continue their studies at Indonesian universities, and scientific writing skills needed to be developed early. However, KIR's efforts to cultivate research and scientific traditions are hampered by the many students interested in this extracurricular activity. To address this issue, the community service team, in collaboration with the person in charge of KIR, selects students who have the potential to participate in KIR and enrols them in research training on September 9-10, 2023, which aims to increase knowledge of the significance of the research being conducted while also attracting students' interest in participating in KIR. Students in research training are tasked with developing simple research logic, carrying out simple research that has been prepared, and reporting on it through presentations and simple scientific writing. During research training, students demonstrate enthusiasm. This primary research training is expected to help strengthen KIR at the Islamic Boarding School Daarul Ukhuwwah Putri 2. However, the KIR supervisor must demonstrate sustainability to continue this essential research activity.